Condition of pro-oxidant system in guinea pigs' bronchi in experimental allergic alveolitis development and their correction with thiotriazolin - Mariana Ljubomurivna Baida; Mariana Muchailivna Fyrduchko-Regeda; Natalia Grugorivna Sementsiv (Kazimierz Wielki University, 2017)
Exogenic allergic alveolitis has been ascribed to multiple inhaled antigens found in a large variety of environmental settings. The immune mechanisms leading to this deases development are still incompletely understood. Initially, believed to be a classes III and IV immune response, we now have a clearer understanding of the complex inflammatory events involved. These include the release of pro inflammatory cytokines and a decrease in the immune control mechanisms via surfactant, dendritic and T-regulatory cells. Free radicals and reactive oxygen species could play a major role in the pathophysiology of allergic alveolitis . Despite the improved understanding, the treatment and outcome of this pathology have not known enough. This work determinate on accumulation of lipid peroxidaton products in the animals` bronchi during experimental allergic alveolitis and corrective effect of antioxidant-thiotriazolin on these indicators.